Incarcerated Colonoscope in a Left Inguinal Hernia During Diagnostic Colonoscopy. Issue 4 (26th April 2021) - Torrealba, Mauricio; Matlock, Robert; Petrun, Branden; Zera, Richard; Malli, Ahmad
ABSTRACT: Colonoscope entrapment in an inguinal hernia is rare and few cases have been described in the literature. We present a 54-year-old patient who underwent a diagnostic colonoscopy which was complicated by incarceration of the colonoscope in a left inguinal hernia. This rare complication occurs more frequently during withdrawal, and our case was unique, given the incarceration of the colonoscope occurred during the insertion phase. Recognizing this scenario is very important to immediately proceed with general anesthesia and surgical consultation for successful nonoperative hernia reduction and colonoscope removal. We recommend reattempting colonoscopy after surgical hernia repair or proceed with computed tomography colonography if appropriate for the indication.